Influence of exchange bias on magnetic losses in CoFeB/MgO/CoFeB tunnel junctions - COEY, JOHN (My University, 2012)
Thestrengthoftheexchangebiasfieldisfoundtoinfluencethelow-frequencymagnetoresistivenoiseassociated with the magnetic reference layer in sputtered-deposited and electron-beam-evaporated CoFeB/MgO/CoFeB tunnel junctions. The noise is due to magnetic losses arising in the reference layer. The losses are parameterized by a phase lag ? which exhibits a nontrivial dependence on the externally applied field. The general trend found among all devices is that the losses are largest in the antiparallel state. The effect of exchange bias on the reference layer?s noise is investigated at a field corresponding to maximum resistance susceptibility, H ref . Higher values for the phase lag at H ref , ? ref , are found in devices having a large exchange bias field. We also observed that H ref and ? ref are larger in devices having thicker seed layers. This characteristic is also evident in double-barrier magnetic tunneljunctions.Prolongedthermalannealingisfoundtodecrease ? ref ,reduce H ref ,andalterthefieldprofileofthe resistance susceptibility of the reference layer to resemble that of a more magnetically soft behavior. In addition to its impact on the magnetoresistive noise, the incorporation of exchange bias layers into the materials stack also affectsthetunnelingmagnetoresistanceratiowithhighervaluesfoundatsmallerexchangebiasfields.Weattribute the magnitude of the magnetic losses, and hence the magnetoresistive noise, from the reference layer to disorder in its magnetic microstructure. Our results indicate that the nature and degree of disorder are correlated to the strengthoftheexchangebiascoupling.Theoriginofthiscorrelationmaybeduetoacompetitionbetweendifferent microstructures among various layers, one that leads to coherent tunneling (large tunneling magnetoresistance) in MgO-based tunneling devices and the other which promotes strong exchange bias coupling. A decrease in the exchange bias either through degradation from thermal treatments or by varying the thickness of the underlying seed layer will lead to less magnetic disorder in the system. We show that the magnetoresistive noise can be used to probe magnetic disorder in exchange-biased devices through the determination of the magnetic losses.
PUBLISHED
Keywords: Physics